Challenges of Reforming the Civil Service in the Post-Soviet Era: The Case of Kyrgyzstan. (December 2014) - Liebert, Saltanat
After the dissolution of the Soviet Union in 1991, Kyrgyzstan went through radical economic reforms to transition from a command to a market-based economy. The governance system had to be rebuilt to reflect the country's shift from socialist ideology to free-market, democratic regime. Despite numerous reforms undertaken by the Kyrgyz Government to restructure its civil service, these efforts have fallen short in creating such a civil service system. To understand the reasons for the limited results achieved by reforms, this article examines formal rules regulating Kyrgyzstan's civil service and assesses how they are implemented in practice. Key aspects of Kyrgyzstan's civil service such as recruitment, selection, promotion, compensation, job security, and performance appraisal are examined. The article juxtaposes formal rules governing key elements of the civil service to the actual practices of the government. In conclusion, I offer an assessment of why civil service reforms produced inadequate results.